Induction of flowering in Arabidopsis through functional peptide-mediated FT mRNA delivery - Masaki Odahara; Maai Mori; Shougo Ishio; Satoshi Kogawara; Keiji Numata (Scientific Reports)
Abstract Flowering is a key developmental event for plants, marking the transition from the vegetative phase to the reproductive phase. Artificial induction of flowering holds great impact on agriculture by accelerating fruit and seed setting. However, to date, only a limited number of externally applicable methods have been established for flowering induction. In this study, we focused on FLOWERING LOCUS T (FT), a pivotal flowering inducer conserved in many flowering plants. We developed a non-transgenic flowering induction system in the model plant Arabidopsis, employing the exogenous introduction of FT mRNA through a functional peptide-mediated delivery. Utilizing the functional peptide BP100-KH9 as a nanocarrier for nucleic acid delivery into plant cells, we confirmed the production of FT protein from the introduced FT mRNA, which was fused with a reporter gene Citrine. The introduction of FT mRNA was also evidenced by the induction of expression of floral genes in treated seedlings, leading to the optimization of the timing for mRNA delivery. Measurement of flowering demonstrated accelerated flowering resulting from the introduction of FT mRNA as indicated by a shortened flowering time and a reduced number of leaves at flowering. This proof-of-concept study proposes an innovative non-transgenic flowering induction method using mRNA delivery.